Various spectrum of lesion in palatine tonsil underwent for tonsillectomy in tertiary care center: a two years retrospective study - Kumar, Gaurav; Sharma, Ritu; Pal, Desh; ., Geeta (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Palatine tonsils are paired masses of lymphoid tissue which act as immunologic barrier against the entry of pathogenic organism into the respiratory and digestive tracts. Despite their protective function, tonsils are prone to infection. Chronic tonsillitis is a disease with repeated attacks of acute tonsillitis or a sub-clinic form of a resistant or poorly treated infection. Objective of the study was to know the various clinico-pathological finding in palatine tonsil underwent for tonsillectomy. Methods: This was a retrospective study where 105 cases (unilateral-15, bilateral-86 and tonsillar biopsy in 04) of histopathologically identified tonsillectomy specimens were included. The available data for all the patients as regards to age, sex and clinical symptoms was collected. Representative bits were taken from formalin fixed tonsillectomy specimens in which hematoxylin and eosin (H and E) staining was done. Results: Amongst the cases, 79 cases showed chronic tonsillitis. Other lesions were chronic tonsillitis with actinomycosis in 11 cases, acute on chronic tonsillitis in 07 cases, granulomatous tonsillitis in 03 cases, Acute ulcerative tonsillitis with micro abscesses in 01 case and Reactive lymphoid hyperplasia in 02 case. Two malignancies were observed - one case of poorly differentiated carcinoma and another case of lymphoma. Conclusions: This study showed that chronic tonsillitis is a common problem facing in all age groups and histopathology play a key role in diagnosing both benign and malignant lesion of tonsil therefore deciding the proper management.